1992
DOI: 10.1002/cne.903210208
|View full text |Cite
|
Sign up to set email alerts
|

Afferent projections to the mammillary complex of the rat, with special reference to those from surrounding hypothalamic regions

Abstract: To better understand the functional organization of the mammillary nuclei, we investigated the afferents to this nuclear complex in the rat with iontophoretically injected wheat germ agglutinin conjugated to horseradish peroxidase. Particular attention was paid to tracing local hypothalamic afferents to these nuclei. Injections into the medial mammillary nucleus (MMN) revealed strong projections from the subicular region, and weaker projections from the prefrontal cortex, medial septum, and the nucleus of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 47 publications
5
37
0
Order By: Relevance
“…A projection to the arcuate nucleus was reported by Zaborsky (1982). (3) We confirmed previous retrograde tracer reports of BSTam projections to the medial preoptic nucleus (Simerly and Swanson, 1986), dorsomedial hypothalamic nucleus (Thompson and Swanson, 1998), "perifornical region" of the lateral hypothalamic area at tuberal levels (Allen and Cechetto, 1993), and lateral supramammillary nucleus (Gonzalo-Ruiz et al, 1992). (4) Retrograde labeling in the BSTam region has been reported after thalamic injections involving the paraventricular nucleus and the adjacent medial part of the mediodorsal nucleus (Groenewegen and Russchen, 1984;Groenewegen, 1988;Chen and Su, 1990) and lateral habenula (Li et al, 1993).…”
Section: Earlier Literaturesupporting
confidence: 88%
“…A projection to the arcuate nucleus was reported by Zaborsky (1982). (3) We confirmed previous retrograde tracer reports of BSTam projections to the medial preoptic nucleus (Simerly and Swanson, 1986), dorsomedial hypothalamic nucleus (Thompson and Swanson, 1998), "perifornical region" of the lateral hypothalamic area at tuberal levels (Allen and Cechetto, 1993), and lateral supramammillary nucleus (Gonzalo-Ruiz et al, 1992). (4) Retrograde labeling in the BSTam region has been reported after thalamic injections involving the paraventricular nucleus and the adjacent medial part of the mediodorsal nucleus (Groenewegen and Russchen, 1984;Groenewegen, 1988;Chen and Su, 1990) and lateral habenula (Li et al, 1993).…”
Section: Earlier Literaturesupporting
confidence: 88%
“…This nucleus receives afferents from and sends projections to the subicular region of the hippocampal formation that travels along the postcommissural fornix. 25,26 Although most in vivo studies to date have indicated that lysosomal enzymes are retrogradely transported in axons, 12,13,27 our data strongly suggests that anterograde transport of bgal is an important component of axonal distribution of this enzyme in the adult GM1-gangliosidosis brain. This notion is supported by a recent study showing identical frequency of anterograde and retrograde movement of GFP-labeled a-L-iduronidase in neurites of primary rat neurons.…”
Section: Mechanisms Of Distribution Of Mouse B-galactosidasementioning
confidence: 67%
“…It is also possible that the MM (in receipt of descending influences from the septo-hippocampal system, see below) mediates activity in PH and SuM. MM has been shown to project to surrounding hypothalamic regions including SuM and PH (Gonzalo-Ruiz et al, 1991). Clearly, more work is needed to distinguish between these possibilities.…”
Section: Discussionmentioning
confidence: 99%